Disinformation and health: fact-checking strategies of Spanish health public institutions through YouTube - Vázquez-Gestal, Montse; Pérez-Seoane, Jesús; Fernández-Souto, Ana-Belén (Frontiers in Communication, 2024)
Through their social media, public institutions address fake news and tackle disinformation that affects both them and the general public. With the rise of online video platforms, the audiovisual format has made its way as a dynamic and engaging format that allows for the creation of narratives to counter distorted information. This circumstance is particularly noticeable in the healthcare sector, where most of the recent fact-checking activity is taking place. METHODOLOGY: Through the analysis of the official YouTube channels of the health departments of all Spanish autonomous communities from 1 January 2021 to 31 December 2023, this paper explores the use of audiovisual fact-checking by Spanish regional governments, and it describes the nature of these videos and the strategies undertaken on that platform to tackle disinformation. RESULTS: Despite the expected territorial disparities, the research findings show that an increasing number of Spanish regional health authorities are using YouTube to fight disinformation. They also show that the videos posted on that platform provide a strong response to fake news, either as a preventive measure or in response to existing publications. DISCUSSION: In the current landscape of declining mass media, where audience dispersion leads a to (sometimes deliberate) fragmentation of discourse, we are confronted with the paradox of being a society with access to a vast amount of information, but not well-informed. Therefore, it is essential to have strong institutions that verify fake content through popular formats.